Probiotic Lactobacillus Rhamnosus GG Protects Against P. Gingivalis And F. Nucleatum Gut Dysbiosis. - Gatej, Simona M; Bright, Richard; Weyrich, Laura S; Marino, Victor; Christophersen, Claus; Gibson, Rachel J; Gully, Neville; Zilm, Peter; Bartold, P Mark (2020)
OBJECTIVES: This study investigated changes induced by Porphyromonas gingivalis and on gastrointestinal histology and gut microbiome in a mouse model of experimental periodontitis. The effect of probiotic Lactobacillus rhamnosus GG (LGG) in altering these changes was also investigated. METHODS: IThirty-six mice were allocated into six groups. Experimental alveolar bone loss was induced by oral inoculation with P. gingivalis and F. nucleatum. LGG was orally inoculated or orally gavaged. Gastrointestinal tissue changes were assessed using histological analysis and immunohistochemistry. Caecal microbiome was analysed by sequencing 16S rRNA genes of caecal content. RESULTS: Inoculation with P. gingivalis and F. nucleatum induced inflammation throughout gastrointestinal tract (p less than 0.05), increased expression of IL-6 in ileum (p = 0.052) and altered composition of caecal microbiome (p less than 0.05) in experimental mice compared to controls. Mice treated with LGG had reduced tissue inflammation in duodenum (p = 0.044) and lowered levels of IL-6 in ileum (p = 0.048) when compared with disease. LGG therapy influenced gut microbiome changes. CONCLUSION: P. gingivalis and F. nucleatum inoculation induced significant changes in intestinal inflammation and caecal microbiome. Oral gavage with LGG exerted a protective effect against intestinal inflammation and limited gut microbiome changes associated with P. gingivalis and F. nucleatum.